Analisis Etika Bisnis Islam dalam Kinerja Pedagang Bakso di Kecamatan Belo - Syarif Hidayatullah; Rosdiana; Umar Sagaf (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to examine the application of Islamic ethics in meatball stall businesses in the Belo District. The business actors referred to in this research are members of the independent meatball stall business group in the Belo District. This is field research using a qualitative approach with a case study strategy. Data collection techniques include observation, interviews, and direct documentation of the relevant subjects. Data validity was ensured through triangulation. The research findings reveal five principles of Islamic business ethics applied in the meatball stalls in the Belo District. First is the principle of tawhid (unity), in which the quality of the offered products is prioritized, and no prohibited (haram) items are used. Second is the principle of balance, ensuring that the prices offered reflect the actual quality and value of the food being sold. Third, the principle of free will is upheld, promoting transparency and the absence of coercion, while allowing customers the freedom to choose from a variety of meatball menu variations at uniform prices, and allowing employees to propose the most popular menu items. Fourth is the principle of responsibility, ensuring excellent service quality, transparent pricing, and responsible waste management. Fifth is the principle of benevolence, guaranteeing fair and adequate support for all customers and transparency in the ordering and payment processes. The conclusion of this research is that meatball stalls in the Belo District have implemented Islamic principles of buying and selling, both in food processing and service delivery, based on Islamic business ethics.